Integrated iron negative electrode, preparation method thereof and nickel-iron battery

By using foam iron and forming iron tetroxide particles through corrosion and annealing, the problems of complex preparation process and insufficient performance of existing iron anode electrode materials are solved, and an iron anode with high specific capacity and good cycle stability are achieved.

CN119560498APending Publication Date: 2025-03-04XINYANG NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411633738.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The preparation process of existing iron negative electrode materials is complex, and the traditional electrode structure and assembly process leads to low specific capacity of iron negative electrodes, poor rate performance and cycle stability.

Method used

Iron foam is used as the basic raw material, nanosheet structure is formed through corrosion and ultrasonic treatment, and then micron-scale iron tetraoxide particles are formed on the surface of the iron foam in situ to prepare integrated iron anode.

Benefits of technology

The high area specific capacity of the iron anode, good rate performance and long-term cycle stability are achieved, the capacity retention rate is above 70.40%, and the stable cycle is more than 300 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560498A_ABST
    Figure CN119560498A_ABST
Patent Text Reader

Abstract

The invention relates to an integrated iron negative electrode, a preparation method thereof and a nickel-iron battery, and belongs to the technical field of electrochemical energy storage device electrode materials. Foam iron is used for preparing the integrated iron negative electrode, and the iron negative electrode is composed of a foam iron framework and ferroferric oxide particles attached to the foam iron framework. The obtained iron negative electrode is integrally formed, does not need to be bonded, integrally shows relatively high area specific capacity, good rate capability and cycling stability, and can be applied to a nickel-iron battery material or other energy storage devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrode materials for electrochemical energy storage devices, and in particular to an integrated iron negative electrode and a preparation method thereof, and a nickel-iron battery. Background Art

[0002] Nickel-iron battery electrode materials are abundant in resources, with simple assembly process, high safety, and less maintenance during use. They are widely used in lighting systems such as railways and mines, and also have great application potential in high-power power batteries and large-scale energy storage. The research on the positive electrode of nickel-iron batteries is relatively mature, but the iron negative electrode is relatively backward, mainly with problems such as poor electrode kinetics and volume expansion during the cycle, which seriously restricts the development of nickel-iron batteries.

[0003] The negative electrode active material of the nickel-iron battery is iron, iron oxide or a mixture thereof. At present, the main method for making the iron negative electrode is to mix the active material and the conductive agent and the binder in a certain proportion and apply them on the current collector. The preparation process is relatively complicated, and the use of the binder is not conducive to electron transmission. At the same time, in order to increase the area specific capacity of the electrode, it is necessary to increase the active material loading per unit area on the current collector, increase the electrode thickness, and further weaken the electrode kinetics. In addition, the electrode material will undergo dissolution and re-deposition during the electrode cycle, resulting in structural deformation of the electrode material and the formation of a passivation layer, which affects the cycle performance of the electrode and the battery.

[0004] Iron foam has good conductivity, unique porous structure and excellent physical and chemical stability, and has great application potential in iron negative electrodes. However, the untreated iron foam has a small specific surface area and is not suitable for direct use as an iron negative electrode. It has been reported that a three-dimensional Fe2O3 thin film electrode can be synthesized using a hydrothermal strategy. This electrode design can improve the electrode kinetics to a certain extent. However, the Fe2O3 material has poor conductivity, low specific capacity, and a complex material synthesis process. It also requires a high temperature and high pressure environment, and has low scale-up potential. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide an integrated iron negative electrode and a preparation method thereof and a nickel-iron battery to solve the problems of complex preparation process of existing iron negative electrode materials, low specific capacity of the iron negative electrode, poor rate performance and cycle stability caused by traditional electrode structure and assembly process.

[0006] On the one hand, the present invention provides an integrated iron negative electrode, which is prepared by using foamed iron; the iron negative electrode is composed of a foamed iron skeleton and ferrosoferric oxide particles attached to the foamed iron skeleton.

[0007] Furthermore, the pore density of the foamed iron is 50-130ppi, the thickness is 1-3mm, and the iron content is ≥98%.

[0008] Furthermore, the ferrosoferric oxide particles are micrometer-sized.

[0009] Furthermore, at 4 mA cm -2 The area specific capacity is 1.12 mAh cm at a current density of -2 Above 32mA cm -2 The specific capacity is 0.81 mAh cm at a current density of -2 The capacity retention rate is above 70.40%, and the stable cycle exceeds 300 cycles.

[0010] On the other hand, the present invention provides a method for preparing an integrated iron negative electrode, which is prepared by subjecting the foamed iron to corrosion and annealing treatments.

[0011] Furthermore, during the corrosion process, the corrosion liquid is dilute hydrochloric acid, and the concentration of the dilute hydrochloric acid is 0.5-1.0M.

[0012] Furthermore, ultrasound is used to assist in the corrosion process, the ultrasonic corrosion time is 30-60 minutes, the frequency of the ultrasound is 20-120kHz, and the power of the ultrasound machine is 300-1200W.

[0013] Furthermore, the annealing temperature is 600°C-1000°C, and the heating rate is 2-10°C min -1 , annealing time is 2-6 hours.

[0014] Preferably, the annealing temperature is 800°C-1000°C.

[0015] The iron negative electrode prepared by the present invention can be used to prepare a nickel-iron battery.

[0016] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0017] 1. The iron negative electrode prepared by the present invention is composed of a foamed iron skeleton and ferroferric oxide particles attached to the foamed iron skeleton, and the whole is a three-dimensional porous structure. The obtained iron negative electrode is formed in an integrated manner, which is different from the traditional electrode assembly process and does not involve the use of conductive agents and the bonding of materials. The iron negative electrode as a whole shows a high area specific capacity, rate performance and cycle stability. -2 The area specific capacity is 1.12 mAh cm at a current density of -2 Above 32mA cm -2 The specific capacity is 0.81 mAh cm at a current density of -2 Above, the capacity retention rate is high at high current density;

[0018] 2. The preparation of the electrode material of the present invention uses foamed iron as the basic raw material. A nanosheet structure is formed on the surface of the foamed iron through corrosion and ultrasonic treatment, and then micron-sized ferrosoferric oxide particles are formed in situ on the surface of the foamed iron through annealing. The foamed iron is effectively utilized in the corrosion process, and no external iron source is required in the electrode preparation process. The ultrasonic process can improve the corrosion efficiency and corrosion uniformity, which is beneficial to improving the size and uniformity of the nanostructure on the surface of the foamed iron. The preparation method of the present invention is completely different from the Fe2O3 thin film electrode synthesized by the existing hydrothermal strategy. The existing hydrothermal preparation method requires a high temperature and high pressure process and has low potential for mass production;

[0019] 3. The foamed iron in the present invention can be purchased at a low price; the entire preparation process is simple in technology, short in cycle, high in efficiency, and suitable for mass production.

[0020] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0022] Figure 1 This is a scanning electron microscope (SEM) image of foamed iron without any treatment;

[0023] Figure 2 This is a SEM picture of the foamed iron prepared in step 2 of Example 1 of the present invention;

[0024] Figure 3 This is a SEM image of the integrated iron negative electrode finally prepared in Example 1 of the present invention;

[0025] Figure 4 is an X-ray electron diffraction (XRD) pattern of the integrated iron negative electrode prepared in Example 1 of the present invention;

[0026] Figure 5 1 is a cyclic voltammetry (CV) characteristic curve of the integrated iron negative electrode prepared in Example 1 of the present invention;

[0027] Figure 6 The constant current charge-discharge (CP) curve of the integrated iron negative electrode prepared in Example 1 of the present invention;

[0028] Figure 7 The cycle performance of the integrated iron negative electrode prepared in Example 1 of the present invention;

[0029] Figure 8 This is a SEM image of the foamed iron prepared in Example 2;

[0030] Fig. 9 CV curve of the integrated iron negative electrode prepared in Example 3 of the present invention;

[0031] Fig.10 CP curve of the integrated iron negative electrode prepared in Example 3 of the present invention;

[0032] Fig.11 This is a SEM picture of the foamed iron after annealing in Comparative Example 3 of the present invention;

[0033] Fig.12 CV curve of the integrated iron negative electrode prepared in Comparative Example 3 of the present invention;

[0034] Fig.13 CP curve of the integrated iron negative electrode prepared in Comparative Example 3 of the present invention;

[0035] Fig.14 This is a practical diagram of a battery constructed using the integrated electrode prepared in Example 1 as the negative electrode and commercial nickel oxide as the positive electrode to light a small light bulb. DETAILED DESCRIPTION

[0036] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0037] Nickel-iron batteries are highly safe and require less maintenance during use, so they are widely used in lighting systems such as railways and mines. The research on the positive electrode of nickel-iron batteries is relatively mature, but the iron negative electrode has problems such as poor electrode kinetics and volume changes of electrode materials during the cycle, resulting in poor electrode specific capacity, rate performance and cycle stability, which limits the development of nickel-iron batteries.

[0038] At present, the production of iron negative electrode is to mix the active material (iron, iron oxide or their mixture) with the conductive agent and binder in a certain proportion and apply them on the current collector. The preparation process is relatively complicated and the use of binder is not conducive to electron transmission. Thicker electrodes will further weaken the electrode kinetics and affect the electrode performance.

[0039] With the development, iron foam has a porous structure and excellent physical and chemical stability, which has gradually attracted attention. However, the untreated iron foam has a small specific surface area and a small specific capacity. Existing reports on the preparation of iron negative electrodes based on iron foam mainly use a hydrothermal synthesis route to synthesize Fe2O3 films on the surface of iron foam. This technical route has a high cost, a complex synthesis route, involves a high temperature and high pressure process, and has low potential for large-scale production.

[0040] Therefore, the present invention provides an integrated iron negative electrode, which is prepared by using foamed iron; the iron negative electrode is composed of a foamed iron skeleton and ferrosoferric oxide particles attached to the foamed iron skeleton.

[0041] Compared with the prior art, the present invention uses foamed iron as the basic raw material. The treated iron negative electrode is composed of a foamed iron skeleton and ferroferric oxide particles attached to the foamed iron skeleton. The obtained iron negative electrode is integrally formed and does not require bonding. Compared with the untreated foamed iron, the amount of active material is significantly increased. The integrated electrode design can provide faster electrode kinetics and structural stability, thereby showing higher area specific capacity, rate performance and cycle stability. At 4mA cm -2 The specific capacity is 1.12 mAh cm at a current density of -2 Above 32 mA cm -2 The specific capacity is 0.81 mAh cm at a current density of -2 The capacity retention rate is above 70.40%.

[0042] Specifically, the pore density of the foamed iron is 50-130ppi, the thickness is 1-3mm, and the iron content is ≥98%.

[0043] Preferably, the pore density of the foamed iron is 95ppi.

[0044] It should be noted that the specific capacity of the final prepared electrode is directly related to the number of voids per unit area (pore density) and thickness of the foamed iron. The higher the pore density and the thicker the foamed iron, the more contact area there is after immersion corrosion and annealing, and the higher the area specific capacity of the prepared iron negative electrode.

[0045] Specifically, the foamed iron has a thickness of 1-3 mm and an iron content of ≥98%.

[0046] Specifically, the foam iron has a thickness of 1.5 mm and is cut into a size of 1 cm×1 cm.

[0047] It should be noted that the thicker the foamed iron is, the more iron it contains per unit area, and the higher the area specific capacity of the prepared iron negative electrode.

[0048] Specifically, the ferrosoferric oxide particles are micrometer-sized.

[0049] Preferably, the size of the ferrosoferric oxide particles is 1-2 μm.

[0050] It should be noted that the prepared integrated iron negative electrode includes a foamed iron skeleton and ferroferric oxide particles loaded on the skeleton. The crystal structure of iron is still retained inside the skeleton, and its surface is covered with ferroferric oxide particles with a size of 1-2μm. The combination of the three-dimensional structure of the foamed iron and the micron-sized ferroferric oxide active material can effectively increase the amount of active material per unit area, enhance the electrical and ion-conducting properties of the electrode, and inhibit the shedding of active materials caused by the volume change of the active materials during the cycle, thus ensuring the high specific capacity, rate performance and good cycle stability of the iron negative electrode.

[0051] In addition, the integrated iron negative electrode of the present invention is obtained by subjecting the foamed iron to corrosion and annealing treatments.

[0052] Specifically, the following steps are included:

[0053] S1. Use a cleaning agent to ultrasonically clean the foam iron to remove dirt and surface oil film;

[0054] S2, placing the cleaned foamed iron in dilute hydrochloric acid for ultrasonic treatment, then rinsing with deionized water and vacuum drying;

[0055] S3: The dried foamed iron is annealed in an inert gas atmosphere and naturally cooled to room temperature to obtain an integrated iron negative electrode.

[0056] Compared with the prior art, the present invention uses foamed iron as a raw material, forms a nanosheet structure on the surface of the foamed iron through hydrochloric acid corrosion and ultrasonic treatment, and then forms micron-sized ferroferric oxide particles on the surface of the foamed iron through annealing. Compared with existing technical routes such as hydrothermal synthesis, the synthesis process proposed by the present invention does not require an external iron source, and the preparation route is simple, efficient, low-cost, and easier to mass-produce.

[0057] Specifically, in step S1, the cleaning agent includes acetone and ethanol.

[0058] It should be noted that the foamed iron is first placed in acetone and ethanol for ultrasonic treatment for 10-15 minutes to remove surface dirt and oil film.

[0059] Specifically, in the etching process of step S2, the etching solution is dilute hydrochloric acid, and the concentration of the dilute hydrochloric acid is 0.5-1.0M.

[0060] It should be noted that the reaction in step S2 can be considered as the reaction of hydrogen ions and foamed iron to generate ferrous iron, which further reacts with oxygen and water to generate ferric iron, and the ferrous iron, ferric iron, water and oxygen react to generate iron hydroxide, which can be specifically represented by the following chemical formula.

[0061] Fe+2H + →Fe 2+ +H2

[0062] 4Fe 2+ +O2+2H2O→4Fe 3+ +4OH -

[0063] Fe 2+ / Fe 3+ +H2O+O2→Fe 2+ Fe 3+ -LDH

[0064] According to the above reaction, the ratio of the product of the foam iron volume and the pore density to the volume of the etching solution is selected to be 1.4. Too high or too low concentration of the hydrochloric acid etching solution will affect the corrosion process of the foam iron. The preferred concentration of hydrochloric acid is 0.5-1.0M.

[0065] Specifically, during the corrosion process, ultrasound is used for assistance, the ultrasound time is 30-60 minutes, the ultrasound frequency is 20-120KHz, and the ultrasound machine power is 300-1200W.

[0066] It should be noted that the purpose of ultrasound is to accelerate the corrosion process of foamed iron and generate larger and more uniform micro-nano structures on the surface of foamed iron. If the ultrasonic corrosion time is too short, the thickness of the micro-nano structure formed will be too small. If the time is too long, the mechanical rigidity of the electrode will be weakened, the electrode will become soft, and the structural stability of the electrode will be affected. The ultrasonic corrosion time is preferably 30-60 minutes.

[0067] Specifically, the vacuum drying temperature is 40-80° C., and the vacuum drying time is 6-12 hours.

[0068] It should be noted that the purpose of vacuum drying is to remove free water on the surface of the material and to increase the crystallinity of the iron hydroxide intermediate, and the morphology is a nanosheet structure supported on the surface of the foamed iron.

[0069] Specifically, the annealing temperature is 600°C-1000°C, and the heating rate is 2-10°C min -1 , annealing time is 2-6 hours.

[0070] It should be noted that the annealing process is essentially the iron hydroxide prepared in the corrosion process dehydrating under an inert atmosphere to become ferroferric oxide, which can be expressed by the following reaction formula:

[0071] Fe 2+ Fe 3+ -LDH→Fe3O4+H2O

[0072] During this process, the morphology of the material changes from flake to granular. The annealing temperature and annealing time will affect the morphology of the final active product. Too low a temperature will cause the morphology of the final product to be uneven. Too high a temperature or too long an annealing time will cause excessive agglomeration of metal oxides, reduce the reaction interface of the active material, and reduce the specific capacity of the electrode. The annealing temperature is preferably 800°C-1000°C, and the annealing time is preferably 2-6 hours.

[0073] Preferably, the annealing temperature is 800°C.

[0074] The iron negative electrode prepared by the present invention can also be applied to nickel-iron batteries. The assembled nickel-iron batteries have good performance and can be used to light small light bulbs.

[0075] In order to more clearly describe the present invention, it is further illustrated by the following examples and comparative examples.

[0076] Example 1

[0077] The preparation of the integrated iron negative electrode comprises the following steps:

[0078] S1. Ultrasonicate the purchased foam iron in acetone for 10 minutes, and then ultrasonicate it in ethanol for 10 minutes to remove surface dirt and oil film;

[0079] The pore density of the foam iron is 95ppi, the thickness is 1.5mm, and it is cut into 1cm×1cm;

[0080] S2, soak the cleaned foam iron in a 1M dilute hydrochloric acid corrosion solution and ultrasonicate for 30 minutes, wash it with deionized water after the ultrasonication, and dry it in a vacuum drying oven at 60°C for 12 hours;

[0081] S3. Place the dried foamed iron in a nitrogen-protected tubular furnace at 5°C min -1 The temperature is raised to 800°C and kept for 2 hours. After annealing, the temperature is naturally lowered to obtain an integrated iron negative electrode.

[0082] Example 2

[0083] The preparation process of Example 2 is substantially the same as that of Example 1, except that the annealing temperature in Example 2 is 600°C.

[0084] Example 3

[0085] The preparation process of Example 3 is substantially the same as that of Example 1, except that the annealing temperature in Example 3 is 1000°C.

[0086] Example 4

[0087] The preparation process of Example 4 is substantially the same as that of Example 1, except that the heating rate in Example 4 is 2°C min -1 .

[0088] Example 5

[0089] The preparation process of Example 5 is substantially the same as that of Example 1, except that the heating rate in Example 5 is 10°C min -1 .

[0090] Example 6

[0091] The preparation process of Example 6 is substantially the same as that of Example 1, except that the ultrasonic etching time in Example 6 is 60 minutes.

[0092] Example 7

[0093] The preparation process of Example 7 is substantially the same as that of Example 1, except that the concentration of the dilute hydrochloric acid etching solution in Example 7 is 0.5M.

[0094] Example 8

[0095] The preparation process of Example 8 is substantially the same as that of Example 1, except that the heat preservation annealing time in Example 8 is 6 hours.

[0096] Comparative Example 1

[0097] Commercial ferrosoferric oxide active material, conductive carbon black and PVDF binder are mixed in a ratio of 8:1:1 and coated on the foamed iron.

[0098] Comparative Example 2

[0099] Untreated iron foam.

[0100] Comparative Example 3

[0101] The preparation process of Comparative Example 3 is substantially the same as that of Example 1, except that step S2 is not included in Comparative Example 3.

[0102] Comparative Example 4

[0103] The preparation process of Comparative Example 4 is substantially the same as that of Example 1, except that step S3 is not included in Comparative Example 4.

[0104] Comparative Example 5

[0105] The preparation process of Comparative Example 5 is substantially the same as that of Example 1, except that the annealing temperature in Comparative Example 5 is 1200°C.

[0106] Comparative Example 6

[0107] The preparation process of Comparative Example 6 is substantially the same as that of Example 1, except that the concentration of the dilute hydrochloric acid etching solution in Comparative Example 6 is 2.0M.

[0108] Comparative Example 7

[0109] The preparation process of Comparative Example 7 is substantially the same as that of Example 1, except that the heat preservation annealing time in Comparative Example 7 is 8 hours.

[0110] Performance Testing

[0111] The electrochemical data of Examples 1-8 and Comparative Examples 1-7 provided by the present invention were tested using a 2M KOH solution as the electrolyte, a saturated calomel electrode as the reference electrode, a platinum sheet electrode as the counter electrode, and the prepared integrated iron negative electrode as the working electrode. The specific test results are shown in Table 1.

[0112] Table 1 Performance test results

[0113]

[0114]

[0115] Combined with Examples 1-8 and Comparative Examples 1-7 and Table 1 and Figure 1-13 , we can see that:

[0116] (1) The surface of untreated foamed iron is relatively smooth at the microscopic level ( Figure 1 ), after corrosion and drying, the surface of the foamed iron is loaded with a uniform flaky structure ( Figure 2 ), the surface of the integrated iron negative electrode prepared after the final annealing treatment is a granular structure, while the surface of the uncorroded iron foam does not form an obvious uniform micro-nano structure after annealing ( Fig.11 ), XRD data( Figure 3 ) indicates that the integrated electrode includes foamed iron and ferroferric oxide active materials;

[0117] (2) In the annealing stage, if the annealing temperature is too high (e.g. 1200°C) or the annealing time is too long (e.g. 8h), the specific capacity of the prepared iron negative electrode will be reduced; in the corrosion stage, if the concentration of the corrosion solution is too high (e.g. 2M), the specific capacity of the electrode will also be reduced;

[0118] (3) Under the preferred conditions, the electrode prepared in Example 1 has high electrochemical activity ( Figure 5 )、High Capacity / Rate( Figure 6 ) and long-term circulation stability ( Figure 7 ) characteristics, the other electrodes (Examples 3-8) prepared using the preferred synthesis conditions all have higher performance ( Fig. 9 , 10, Table 1). At 4 mA cm -2 The specific capacity is 1.12 mAh cm at a current density of -2 Above 32 mA cm -2 The specific capacity is 0.81 mAh cm at a current density of -2 The capacity retention rate is above 70.40%.

[0119] The capacity is better than the iron negative electrode prepared by the traditional method (Comparative Example 1), and is significantly better than the untreated foamed iron electrode (Comparative Example 2), the lack of corrosion process (Comparative Example 3, Fig.12 , 13 ) or the electrode prepared without annealing process (Comparative Example 4), showing the superiority of the integrated iron negative electrode and the preparation method thereof provided by the present invention.

[0120] application

[0121] The integrated electrode prepared in Example 2 was used as the negative electrode, and commercial nickel oxide, conductive carbon black and binder were coated on nickel foam in a ratio of 8:1:1 as the positive electrode. A full battery test was assembled in a 2M KOH solution. Two full batteries were connected in series to light up a small light bulb, such as Fig.14 As shown, it is shown that the integrated electrode constructed by this method has good performance and can be fully used in nickel-iron batteries.

[0122] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. An integrated iron negative electrode, characterized in that: An integrated iron negative electrode is prepared by using foamed iron; the iron negative electrode is composed of a foamed iron skeleton and ferrosoferric oxide particles attached to the foamed iron skeleton.

2. The integrated iron negative electrode according to claim 1, characterized in that: The foamed iron has a pore density of 50-130 ppi, a thickness of 1-3 mm, and an iron content of ≥98%.

3. The integrated iron negative electrode according to claim 1, characterized in that: The ferrosoferric oxide particles are micron-sized.

4. The integrated iron negative electrode according to claim 1, characterized in that: At 4 mA cm -2 The area specific capacity is 1.12 mAh cm at a current density of -2 Above 32mA cm -2 The specific capacity is 0.81 mAh cm at a current density of -2 The capacity retention rate is above 70.40%, and the stable cycle exceeds 300 cycles.

5. A method for preparing the integrated iron negative electrode according to any one of claims 1 to 4, characterized in that: The following steps are involved: The foamed iron is subjected to corrosion and annealing treatment to obtain an integrated iron negative electrode.

6. The method for preparing the integrated iron negative electrode according to claim 5, characterized in that: During the corrosion process, the corrosion liquid is dilute hydrochloric acid, and the concentration of the dilute hydrochloric acid is 0.5-1.0M.

7. The method for preparing the integrated iron negative electrode according to claim 5, characterized in that: During the corrosion process, ultrasound is used for assistance. The ultrasonic corrosion time is 30-60 minutes, the frequency of the ultrasound is 20-120kHz, and the power of the ultrasound machine is 300-1200W.

8. The method for preparing the integrated iron negative electrode according to claim 5, characterized in that: The annealing temperature is 600°C-1000°C, and the heating rate is 2-10°C min -1 , annealing time is 2-6 hours.

9. The method for preparing the integrated iron negative electrode according to claim 8, characterized in that: The annealing temperature is 800°C-1000°C.

10. A nickel-iron battery, characterized in that: It comprises the iron negative electrode described in any one of claims 1 to 4 or the iron negative electrode prepared by the preparation method described in any one of claims 5 to 9.